1996
DOI: 10.1111/j.1365-2648.1996.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and sources of information for women with breast cancer: a follow‐up study

Abstract: This paper reports a study which examined the specific information needs and sources of information for 105 women with breast cancer at two time points, the time of diagnosis and a mean of 21 months from diagnosis. At diagnosis the priority information needs concerned survival issues. Further from diagnosis survival issues were still a concern, but information about the risk to family members of getting breast cancer showed a significant increase in importance. Information about sexual attractiveness was ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
218
3
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(235 citation statements)
references
References 16 publications
(19 reference statements)
9
218
3
5
Order By: Relevance
“…Luker and colleagues 33 found that 105 patients with breast cancer reported gaining useful information at the time of diagnosis from medical professionals. At an average of 21 months later, however, this sample reported gaining information primarily from the popular media and often reported discomfort in requesting information from medical providers.…”
Section: Table 1 Myths Of Treatment Completionmentioning
confidence: 99%
“…Luker and colleagues 33 found that 105 patients with breast cancer reported gaining useful information at the time of diagnosis from medical professionals. At an average of 21 months later, however, this sample reported gaining information primarily from the popular media and often reported discomfort in requesting information from medical providers.…”
Section: Table 1 Myths Of Treatment Completionmentioning
confidence: 99%
“…At the conclusion of treatment, medical care and support may decrease owing to the belief that the worst is over and that the patient does not require ongoing assistance [23]. Patients indicate some discomfort requesting information from medical providers as time since diagnosis increases and instead seek information from popular media [24]. Breast cancer patients report a significant decrease in the helpfulness of emotional, informational and decisionmaking support from family, friends and health providers within the first year of diagnosis [19] and patient satisfaction with healthcare decreases over time [25].…”
mentioning
confidence: 99%
“…Information preferences were associated with age, education, race, and medical status. Since that seminal study, a number of others have explored the information needs of cancer survivors [5,[11][12][13][14][15][16][17][18][19]. These studies identified other patient factors that influenced information needs including gender, employment status, coping style, type of cancer, and time since diagnosis.…”
Section: Introductionmentioning
confidence: 99%